Toolkit for Impact Evaluation of Public Credit Guarantee Schemes for SMEs - World Bank Group (World Bank, Washington, DC, 2018)
Limited access to finance, particularly bank credit, is a long-standing hurdle for Small and Medium Enterprise (SMEs), with varying severity of financing constraints across countries. SMEs face higher transaction costs and higher risk premiums since they are typically more opaque and have less or inadequate collateral to offer. Financing is also a major constraint in advanced economies, where financing gaps for SMEs were exacerbated by the 2008-2009 financial and economic crisis. SMEs face higher transaction costs and higher risk premiums since they are typically more opaque and have less or inadequate collateral to offer. These market failures and imperfections provide the rationale for government intervention in SME credit markets. An increasingly popular form of government intervention is represented by credit guarantee schemes (CGSs). These are specialized institutions or programs set up by the government which pledge to repay some or the entire loan amount to the lender in case of default of the SME borrower. The toolkit for impact evaluation of public credit guarantee schemes for SMEs has been created with the objective of identifying a set of uniform methodologies for assessing the financial and economic impact of public CGSs as systematically and objectively as possible. After the introductory Module, the Toolkit is divided in nine parts. Module 2 provides an overview of impact evaluation and introduces different modalities of impact evaluation such as prospective and retrospective evaluations. Module 3 provides a roadmap for designing and implementing a CGS impact evaluation. The later modules (5 through 10) finally touch upon some operational steps to implement an impact evaluation such as collecting data, setting the evaluation team, budgeting and timing for the evaluation, and producing and disseminating the results.